Leadership styles and job performance in medical professionals at hospital Vitarte – Lima, 2018: Estilos de liderazgo y desempeño laboral en médicos del hospital Vitarte – Lima 2018 - Bedriñana Sotomayor, José Luis (2023)
Objective: To determine the relationship between leadership styles and work performance of the medical staff of Hospital Vitarte Lima, 2018. Methods: Descriptive, correlational and cross-sectional study. A non-probabilistic purposive sampling was done by selecting 64 workers. And data collection was done through a previously validated questionnaire and internal consistency by Cronbach's alpha. Results: The descriptive statistics determined a 50 % in the Democratic Leadership Style of the dimensions and a level higher than 60 % for Job Performance, the inferential statistics through the Hypothesis Test by Spearman's correlation coefficient (rho = 0.85) showed a high positive correlation in both variables. Conclusion: There is a positive correlation between the dimensions Democratic Leadership Style and work performance, so it is recommended the creation of quality improvement projects and training for workers.